2003
DOI: 10.1079/phn2002434
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Australian food-frequency questionnaire with diet records: implications for nutrition surveillance

Abstract: Objectives: To compare a widely used Australian food-frequency questionnaire (FFQ) with diet records and consider the results in relation to its use in nutrition surveillance. Design: Inter-method reliability study. Setting: A randomised trial in subjects with past asbestos exposure. Subjects: Seventy-two adults living in Western Australia. Methods: A semi-quantitative FFQ developed by the Commonwealth Scientific Industrial Research Organisation in South Australia was administered after the completion of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
3
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 30 publications
2
61
3
2
Order By: Relevance
“…However, it is a booklet that takes 45 min to complete and has to be manually coded before the manual data entry, increasing both the respondent burden and the resources required to analyse the FFQ. The CSIRO FFQ had been validated by ourselves and others (7)(8)(9)(10) .…”
Section: Food Frequency Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…However, it is a booklet that takes 45 min to complete and has to be manually coded before the manual data entry, increasing both the respondent burden and the resources required to analyse the FFQ. The CSIRO FFQ had been validated by ourselves and others (7)(8)(9)(10) .…”
Section: Food Frequency Questionnairementioning
confidence: 99%
“…However, it is a booklet that takes 45 min to complete and has to be manually coded before the manual data entry, increasing both the respondent burden and the resources required to analyse the FFQ. The CSIRO FFQ had been validated by ourselves and others (7)(8)(9)(10) .The objectives of the present study were to examine the utility of the shorter FFQ compared with the longer FFQ and to establish the agreement between the CSIRO FFQ and the CCV FFQ, as there are advantages of reduced respondent burden and fewer professional resources of using a machine-readable FFQ. …”
mentioning
confidence: 98%
“…Other reliability studies of FFQs in adolescents, reported similar ranges of kappa values and correlation coefficients (24,37,39) . The results of the validation analyses showed that mean differences for beverage intake (frequencies, absolute intakes and healthy beverage ratio) were small.…”
Section: Discussionmentioning
confidence: 54%
“…At the time of commencement of this study, the number of validated iodine FFQs was limited but of those that did exist, compared to dietary records, the level of iodine intake established by FFQs was generally overestimated (50). Food frequency questionnaires are unreliable when determining absolute specific RDI cut-offs and therefore may not reflect precise dietary amounts (50,51). They are useful, however, in classifying groups into high or low intakes as well as identifying the main dietary sources of iodine (50).…”
Section: Assessment Of Dietary Iodine Intakementioning
confidence: 99%
“…They are useful, however, in classifying groups into high or low intakes as well as identifying the main dietary sources of iodine (50). It is for this reason, FFQs were used to estimate the ranking dietary intake of individuals but are not used to determine absolute measures of dietary intake (51). The method, however, is heavily reliant on memory recall, and may be limited to subjective interpretation of portion sizes leading to over or under estimates of micronutrient intake (46, 52).…”
Section: Assessment Of Dietary Iodine Intakementioning
confidence: 99%